2010
DOI: 10.1142/s1088424610002410
|View full text |Cite
|
Sign up to set email alerts
|

Comparative DFT study for molecular geometries and spectra of methyl pheophorbides-a: test of M06-2X and two other functionals

Abstract: The recent interest in the application of density functional theory (DFT) has prompted us to test several functions in molecular geometries of methyl pheophorbides-a (MPa), an important starting material in photodynamic therapy (PDT). In this study, we report on tests for three popular DFT methods: M06-2X, B3LYP, and LSDA. Based on the standard deviation and the mean value, and by using the difference between optimized calculated value and experimental value in geometries, we drew the following conclusions: M0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…9, [15][16][17] This method characterizes the chlorin conformation in terms of equivalent displacements along the normal coordinates of the chlorin macrocycle. Typically, the largest static distortions of the chlorin macrocycle occur along the softest normal modes; hence, the greatest contributors to the nonplanar distortion are the lowest-frequency normal coordinates of each out-of-plane symmetry type (i.e., B1u, B2u, A2u, Eg, and A1u).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…9, [15][16][17] This method characterizes the chlorin conformation in terms of equivalent displacements along the normal coordinates of the chlorin macrocycle. Typically, the largest static distortions of the chlorin macrocycle occur along the softest normal modes; hence, the greatest contributors to the nonplanar distortion are the lowest-frequency normal coordinates of each out-of-plane symmetry type (i.e., B1u, B2u, A2u, Eg, and A1u).…”
Section: Methodsmentioning
confidence: 99%
“…9(a)-17 Choe et al 17 reported the geometry of methyl pheophorbide-a and compared the validity of M06-2X with two other functional calculations, namely, B3LYP and LSDA. The main problem with DFT calculations is that the exact functionals for exchange and correlation are unknown, except for free electron gases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…60 Geometry optimizations were performed with the M06-2X [61][62][63] functional using the 6-311++G(d,p) basis set. The M06-2X functional was chosen based on the work of Zhao and Thrular 64 that showed that the M06-2X functional describes well the cation-π interaction.…”
Section: Computational Detailsmentioning
confidence: 99%
“…DFT has been extensively utilized to study various aspects of porphyrin and chlorin macrocycle [9][10][11][12][13][14][15][16][17][18]. DFT calculation is preferred because it includes the effects of electron correlation in model chemistry.…”
Section: Introductionmentioning
confidence: 99%